Аналіз проблематики функціонування та перспективи розвитку спрощеної системи оподаткування в Україні - Котенко, Людмила Миколаївна; Фадєєва (Коптєва), Ганна Миколаївна (Харківський державний університет харчування та торгівлі, 2014)
Проведено аналіз законодавства, що регламентує справляння єдиного податку в Україні. Виявлено недоліки у механізмі функціонування спрощеної системи оподаткування та надані рекомендації щодо їх усунення, які сприятимуть наближенню вітчизняного податкового законодавства до норм податкового законодавства розвинутих країн. Також розкрито низку інновацій, які дозволять зробити спрощену систему більш зручною для підприємців.

Special taxation regimes used in Ukrainian practice differ in low fiscal and incentive effect. Significant revenue losses, low level of small business sector in national economy, slow pace of investment and innovation development, the presence of social problems, etc. demonstrate this. The purpose of the research is to analyze the legislation regulating the single tax levy for the presence of shortcomings in it, and the prospects of its development. The shortcomings in the mechanism of the simplified tax system are: - disparity between the Tax Code of Ukraine norms and other normative legal acts in the definition of taxpayers who may use the simplified tax system; - the order of the recognition of a single tax payer income in the terms of repayable financial assistance; - the order of granting vacation time and sick leaves for single tax payers and taxpayers of the II group, who do not use wage workers’ labour; - overdue accounts payable cancellation by single taxpayers, who are juridical persons, etc. This article informs about a number of innovations which made it possible to make the simplified tax system more convenient for the entrepreneurs. Thus, the current simplified system of taxation, accounting and reporting in Ukraine has flaws and doubtful aspects. The elimination of these shortcomings and more thorough presentation of legislation in the laws and regulations contribute to the approximation of national tax legislation to tax legislation of the developed countries as well as further improvement of the simplified tax system to facilitate the development of small and medium enterprises in Ukraine.
Analysis of problems and prospects of the operation of the simplified taxation system in Ukraine
Keywords: податок єдиний; підприємець; законодавство; заборгованість кредиторська; Пенсійний фонд України; відпустка; flat tax; entrepreneur